Effects of Dietary Maltol on Innate Immunity, Gut Health, and Growth Performance of Broiler Chickens Challenged With Eimeria maxima - Park, Inkyung; Goo, Doyun; Nam, Hyoyoun; Wickramasuriya, Samiru S.; Lee, Kichoon; Zimmerman, Noah P.; Smith, Alexandra H.; Rehberger, Thomas G.; Lillehoj, Hyun S. (Frontiers in Veterinary Science, 2021)
Two studies were conducted to evaluate the effects of maltol on innate immunity, gut health, and enteric infection. In the first study, an in vitro culture system was used to evaluate the effects of maltol on the innate immune response of chicken macrophage cells (CMC), gut integrity of chicken intestinal epithelial cells (IEC), anticoccidial ability against E. maxima, and differentiation of quail muscle cells and primary chicken embryonic muscle cells. In the second in vivo study, the dietary effect of maltol on disease parameters, including growth performance, gut lesion, epithelial cell integrity, fecal oocyst shedding, and host immune response, after oral infection with E. maxima was evaluated by feeding high and low doses to newly hatched commercial broiler chickens, to determine the applicability of maltol as a postbiotic. In vitro, maltol increased (P < 0.001) the gene expression levels of occludin, ZO-1, and MUC2 in IEC compared to that in the control group and increased (P < 0.001) IL-1β and IL-8 levels in the LPS-stimulated CMC compared to that in the non-LPS groups, regardless of the dose administered. Maltol also decreased (P < 0.001) the survival rate of sporozoites of E. maxima. In vivo, the HI (10.0 mg/kg feed) and LO (1.0 mg/kg feed) maltol groups increased (P < 0.001) the BW following E. maxima infection compared to that in the NC group. The HI group decreased the gut lesion score (P = 0.024), jejunum gene expression of TNFSF15 (P = 0.048), and IL-1β (P = 0.032) and fecal oocyst shedding (P < 0.001) in E. maxima-infected chickens. In conclusion, maltol administration improved the immune responses of IEC and CMC in vitro, and improved the growth performance, intestinal immune response, and gut barrier integrity of chickens infected with E. maxima in vivo. These results demonstrate the beneficial effects of dietary maltol in the enhancement of growth performance, gut health, and disease resistance in coccidiosis and the applicability of maltol as a postbiotic for the replacement of antibiotic growth promoters in commercial poultry production.